2020
DOI: 10.1111/ajpy.12293
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to companion animals and loneliness in Australian adolescents

Abstract: Objective: Loneliness can have detrimental consequences for adolescent mental health and wellbeing. Previous, international, investigations of attachment to companion animals have reported positive effects of such bonds on adolescent loneliness. The current study aimed to determine the relationship between companion animal attachment and loneliness among Australian adolescents. Method: A geographically diverse sample of Australian adolescents (n = 283) was gathered via an online survey. Participants responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
10
0
1
Order By: Relevance
“…Antonacopoulos and Pychyl [60] hypothesized that highly attached pet owners may spend more time with their companion animals and, thus, engage in less social interaction with humans, leading them to feel more socially isolated. This is supported by a study conducted by Hartwig and Signal [61], which found that youth who were primary caretakers of their pet reported lower social support scores. Hartwig and Signal [61] also found that attachment to pets was positively associated with loneliness for youth who were primary caretakers.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Antonacopoulos and Pychyl [60] hypothesized that highly attached pet owners may spend more time with their companion animals and, thus, engage in less social interaction with humans, leading them to feel more socially isolated. This is supported by a study conducted by Hartwig and Signal [61], which found that youth who were primary caretakers of their pet reported lower social support scores. Hartwig and Signal [61] also found that attachment to pets was positively associated with loneliness for youth who were primary caretakers.…”
Section: Discussionsupporting
confidence: 54%
“…This is supported by a study conducted by Hartwig and Signal [61], which found that youth who were primary caretakers of their pet reported lower social support scores. Hartwig and Signal [61] also found that attachment to pets was positively associated with loneliness for youth who were primary caretakers. Additionally, evidence from a longitudinal study that found that, after obtaining a pet dog, youths initially received more visits from friends; however, 12 months after getting the dog, youths who were more highly attached to their dog reported spending more time alone and less time with friends and family as compared to youths that were not highly attached to their dog [62].…”
Section: Discussionsupporting
confidence: 54%
“…The current study investigated the impact of pets on mental health and wellbeing in Malaysia during the MCO in 2020. The situation triggered a unique opportunity to study the effect of pets on their owners during this prolonged and imposed social isolation [ 22 , 23 ] and the experience of loneliness [ 24 ]. The Department of Statistical Malaysia (DOSM) published the country’s demographic structure in the first quarter of 2021 showing a population in Malaysia of 32.75 million, with 16.83 million males and 15.92 million females.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of satisfaction as an element of positive youth‐pet relationships suggests that emotional and social support may be a key underlying factor associated with socio‐emotional well‐being. The measures of pet relationships in this study do not capture responsibility for the care of a pet, which has been demonstrated in prior research to impact relationship quality (Hartwig & Signal, 2020). Teasing out the relative impacts of time spent interacting/playing with a pet and engaging in responsibility for care is a fruitful direction for future research.…”
Section: Discussionmentioning
confidence: 97%